Dynamic Experiment of Parts of Car Tyres. (2017) - Krmela, Jan; Krmelová, Vladimíra
Abstract: The paper deals with method for dynamic experiment of parts of car radial tyres. The aim of research work of authors is also propose and evaluate the experimental procedures for cyclic loading of selected parts of tyres with textile reinforcement and rubber matrix. The universal testing device Autograph AG-X plus 5 kN – Schimadzu with video-extensometer with test mode Control of software Trapenzium X was used for experiments. The five cycle loop were used. Every cycle loop consisted of five cycles, every cycle is defined as loading to certain percent of elongation and unloading to certain percent of elongation. The fifth cycle can be used as steady state for comparison of behaviour between specimens with different cord angle. Knowledge about characteristics of dynamic experiment such as cyclic tensile loading is necessary for the verification analysis between experiments and computational modeling of tyres by FEA. Also the determination of material parameters from experimental data will be used as input data to computational modeling of tyres. The results will be also applied in the case of the composites with the woven and nonwoven textile reinforcement and moreover, these results can be used in such conditions where the mentioned composites are exposed to the cyclic loading at unsteady temperature: tyre casing, conveyor belts, etc.